2016
DOI: 10.1016/j.clon.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival from Ovarian Cancer in Patients Treated in Phase III Trial Active Cancer Centres in the UK

Abstract: The data suggest that international survival statistics are achieved in UK regional cancer centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These data compare favourably with two large, randomizedcontrolled trials in women with advanced EOC where resection rates varied significantly between centres [3, 13] yet remain lower than those reported by other centres both nationally and internationally [10,11,14]. The median PFS of 14.3 months is similar to those reported in other UK populations and several international trials [10,15]. Despite a significant increase in the number of bowel resections (20.5% in group 1 vs. 42.7% in group 2) and an associated reduction in pelvic residual disease, a more aggressive surgical approach did not significantly improve rates of complete or optimal cytoreduction and no significant improvement in progression free survival was seen between the two groups.…”
Section: Resultssupporting
confidence: 77%
“…These data compare favourably with two large, randomizedcontrolled trials in women with advanced EOC where resection rates varied significantly between centres [3, 13] yet remain lower than those reported by other centres both nationally and internationally [10,11,14]. The median PFS of 14.3 months is similar to those reported in other UK populations and several international trials [10,15]. Despite a significant increase in the number of bowel resections (20.5% in group 1 vs. 42.7% in group 2) and an associated reduction in pelvic residual disease, a more aggressive surgical approach did not significantly improve rates of complete or optimal cytoreduction and no significant improvement in progression free survival was seen between the two groups.…”
Section: Resultssupporting
confidence: 77%
“…Ovarian cancer is one of the most common types of tumor in women worldwide, and exhibits increasing morbidity and mortality rates (1,2). Despite medical advances in surgical techniques, radiation, chemotherapy and gene target therapy, the five-year survival rate of patients with ovarian cancer remains poor (3,4). Resistance to anti-ovarian cancer therapies is a major issue in patients with recurrent ovarian cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Work within NCRAS is underway to identify patients in whom tumour BRCA testing was performed. Evidence strongly suggests that patients want to participate in research trials, those who do have better outcomes, and centres with greater research recruitment deliver better outcomes for patients [9]. Data on research participation are collected routinely through the collaborative research networks and can be assessed and reported.…”
Section: Best Practice Solutionsmentioning
confidence: 99%
“…Particular concerns are around those patients with widespread advanced, or relapsed, disease who require specialised abdominal surgery. Limited infrastructure resources, including operating theatre time, intensive care capacity, gaps in surgical skills training, workforce pressures, and diagnostic delays, are key contributors to suboptimal care despite the implementation of a centralised model [6][7][8][9][10]. The effect of the limitations are reflected in ovarian cancer survival statistics, with the UK lagging behind comparable countries [11].…”
Section: Introductionmentioning
confidence: 99%